Mission: Impossible 2 2 - Woo, John, 1948-; Moore, Ronald D.; Braga, Brannon; Towne, Robert; Cruise, Tom, 1962-; Scott, Dougray, 1965-; Newton, Thandiwe, 1972-; Zimmer, Hans (Hollywood, Calif. : Paramount Home Video, 2006)
When renegade agent Sean Ambrose (Scott) threatens to release the deadly "Chimera" virus into the population, it is up to IMF agent Ethan Hunt (Cruise) and his beautiful partner Nyah Hall (Newton) to stop him.
Based on the television series created by Bruce Geller.
Originally released as a motion picture in 2000.
Features: "Behind the mission" exclusive cast and crew interviews, "Mission incredible" stunts featurette, "Impossible shots" 11 amazing stunt sequences including exclusive interviews with Tom Cruise, John Woo, and stunt coordinator Brian Smrz, commentary by the director John Woo, "I disappear" Metallica music video, alternate title sequence, "Mission improbable" a M:I-2 inspired parody from the MTV movie awards, dynamic interactive menus, scene selection; DVD-ROM features: PCFriendly, agent dossiers, mission locations, "Legend of Chimera", M:I-2 tech tools, M:I-2 DVD online.
Director of photography, Jeffrey L. Kimball ; visual effects supervisor, Richard Yuricich ; production design, Tim Sanders ; film editors, Christian Wagner, Steven Kemper ; music, Hans Zimmer.
Tom Cruise, Dougray Scott, Thandie Newton, Richard Roxburgh, John Polson, Brendan Gleeson, Radé Sherbedgia, Ving Rhames.
MPAA rating: PG-13.
Keywords: Spies -- Drama; Terrorists -- Drama; Film sequels; Video recordings for the hearing impaired; Fiction films; Feature films